Real-time temperature estimation and monitoring of HIFU ablation through a combined modeling and passive acoustic mapping approach. - Jensen, C; Cleveland, R; Coussios, C (2013)
Passive acoustic mapping (PAM) has been recently demonstrated as a method of monitoring focused ultrasound therapy by reconstructing the emissions created by inertially cavitating bubbles (Jensen et al 2012 Radiology 262 252-61). The published method sums energy emitted by cavitation from the focal region within the tissue and uses a threshold to determine when sufficient energy has been delivered for ablation. The present work builds on this approach to provide a high-intensity focused ultrasound (HIFU) treatment monitoring software that displays both real-time temperature maps and a prediction of the ablated tissue region. This is achieved by determining heat deposition from two sources: (i) acoustic absorption of the primary HIFU beam which is calculated via a nonlinear model, and (ii) absorption of energy from bubble acoustic emissions which is estimated from measurements. The two sources of heat are used as inputs to the bioheat equation that gives an estimate of the temperature of the tissue as well as estimates of tissue ablation. The method has been applied to ex vivo ox liver samples and the estimated temperature is compared to the measured temperature and shows good agreement, capturing the effect of cavitation-enhanced heating on temperature evolution. In conclusion, it is demonstrated that by using PAM and predictions of heating it is possible to produce an evolving estimate of cell death during exposure in order to guide treatment for monitoring ablative HIFU therapy.